2016
DOI: 10.2112/si76-008
|View full text |Cite
|
Sign up to set email alerts
|

Topobathymetric Elevation Model Development using a New Methodology: Coastal National Elevation Database

Abstract: During the coming decades, coastlines will respond to widely predicted sea-level rise, storm surge, and coastal inundation flooding from disastrous events. Because physical processes in coastal environments are controlled by the geomorphology of over-the-land topography and underwater bathymetry, many applications of geospatial data in coastal environments require detailed knowledge of the near-shore topography and bathymetry. In this paper, an updated methodology used by the U.S. Geological Survey Coastal Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 25 publications
2
52
0
2
Order By: Relevance
“…In the center of Bulls Bay, located near the city of Charleston SC, the maximum storm tide was about 5.3 m, which was induced by Hurricane Hugo (1989). Our results satisfactorily agree with those from Dietsche et al (2007) who found that Hurricane Hugo generated a water level of between 4.3 and 5.1 m in the middle of Bulls Bay. HWMs surveyed by the U.S. Army Corps of Engineers (USACE) show that the water level on the bay's floodplain exceeded 5.5 m above MSL (Schuck- Kolben, 1990).…”
Section: Storm Surge and Storm Tidesupporting
confidence: 92%
See 1 more Smart Citation
“…In the center of Bulls Bay, located near the city of Charleston SC, the maximum storm tide was about 5.3 m, which was induced by Hurricane Hugo (1989). Our results satisfactorily agree with those from Dietsche et al (2007) who found that Hurricane Hugo generated a water level of between 4.3 and 5.1 m in the middle of Bulls Bay. HWMs surveyed by the U.S. Army Corps of Engineers (USACE) show that the water level on the bay's floodplain exceeded 5.5 m above MSL (Schuck- Kolben, 1990).…”
Section: Storm Surge and Storm Tidesupporting
confidence: 92%
“…The bottom friction is parametrized using the hybrid nonlinear bottom friction law so that the friction coefficient is constant in deep waters whereas, in shallow waters, it increases as the water depth decreases. The friction coefficient in deep waters C F (i.e., the minimum friction coefficient) is set to a constant of 0.0025, a widely used value in ocean circulation models (e.g., Akbar et al, 2017;Dietsche et al, 2007). Our sensitivity analysis also showed that the model with C F 5 0.0025 outperforms the model with C F 5 0.0015 or 0.0035.…”
Section: Circulation Model Adcircmentioning
confidence: 68%
“…Finally, cross‐shore elevation profiles were extracted from a combined topographic and bathymetric DEM at each transect (Danielson et al, ; Thatcher et al, ). Using the elevation profiles, the remaining model inputs were estimated, which included average foreshore beach slope ( β ), cliff height ( h c ), nearshore slope from 3 to 10 m depth ( α ), and cliff toe elevation ( E j ).…”
Section: Methodsmentioning
confidence: 99%
“…MARXAN; Watts et al., ), to direct regional and larger scale management plans, and to parameterize models with baseline conditions from which predictions can be made and scenarios tested (Chaumillon et al., ; Roscoe, ). The iterative development of models also requires the continued input of interdisciplinary knowledge (Danielson et al., ; Munoz, Marquez, & Real, ). For example, ecosystem models are only just beginning to include dynamic representation of genetic adaptations that improve a species or individuals’ resilience to climate change—previously adaptations had to be identified by genetic sequences or other direct observations and the information then integrated into model parameterizations or user defined scenarios (Munday, Donelson, & Domingos, ).…”
Section: Trends and Limitations In The Exchange Of Interdisciplinary mentioning
confidence: 99%